Bone stress and damage distributions during dental implant insertion: a novel dynamic FEM analysis. Issue 12 (30th August 2022) - Demirbas, Ahmet Emin; Ekici, Recep; Karakaya, Mustafa; Alkan, Alper
Abstract: The objective of this research was to evaluate the stress and damage occurring on the bone model of D2 quality during implant insertion procedure using a novel dynamic finite element analysis (FEA) modeling. Three-dimensional finite element method was used to simulate the implant placement into the mandible. The cross-sectional model of the implant was created in SolidWorks 2007 software. The implant model was created to resemble a commercially available fine thread bone level dental implant (Bilimplant®, Turkey). 3 D bone models created with and without cortical bone drilling were specified according to D2 bone (Misch's Bone Classification) with a 1.5 mm cortical bone thickness. The stress patterns in both cancellous and cortical crestal bone were examined during implant insertion by using a novel dynamic FEA in ABACUS/Explicit (ABAQUS/Explicit version 6.14). According to the results of the dynamic FEA, it was reduced stress and damage significantly on the crestal bone region using the cortical drill before the implantation. Also, implant placement time was shorter when the cortical drill was used. The present research is a pilot study using a novel dynamic FEM to model and simulate the dental implant insertion process. This study showed that the use of cortical drills decreased the stress in the bone, especially crestal region, and shortened the whole implant insertion time.